PELATIHAN BUDIDAYA SIRIH HUTAN DAN PENGOLAHANNYA SEBAGAI BAHAN BAKU PEMBUATAN INSEKTISIDA BOTANI DI NAGARI SIKABU BUKIK KABUPATEN PADANG PARIAMAN - Lina, Eka Candra; Nelly, Novri; Refdi, Cesar Welya; Dinata, Uyung Gatot S; Fithri, Prima (LPPM Universitas Andalas, 2024)
Community service for Bumnag Sehati and Saiyo Sakato highlights training and post-harvest cultivation of forest betel plants (Piper aduncum) as raw materials for botanical insecticides. This activity involves outreach to farmers about the economic potential of forest betel plants and cultivation and management techniques. As a result, farmers understand the economic value and how to manage these plants, increase their knowledge and open up opportunities to increase income through the use of local resources. The recommendations provided include optimal use of forest betel plants, development of new products, ongoing education and training, as well as strengthening cooperation with various parties. The aim of the activity is to provide an in-depth understanding of forest betel cultivation techniques and post-harvest for making botanical insecticides. Train participants in the process of cultivating, harvesting and processing forest betel effectively to produce quality raw materials. Introducing the latest technology in forest betel cultivation and processing to increase efficiency and yield. Providing an environmentally friendly alternative for pest control through forest betel-based botanical insecticides. The activity method used is the delivery of material regarding the theory of forest betel cultivation, post-harvest processes, and making botanical insecticides through lecture sessions. The result of this activity is that participants gain practical skills in cultivating forest betel and the process of making botanical insecticides. Participants understand the importance of forest betel in making insecticides and the optimal way to process it. The conclusion that can be obtained from this activity is that the use of forest betel as a raw material for botanical insecticides provides an environmentally friendly alternative for pest control. Continued efforts are needed for the development of cultivation techniques, as well as further research into the effectiveness and market acceptance of forest betel-based botanical insecticides.